Organizational internal factors and construction risk management among Nigerian construction companies - Adeleke, A.Q.; Bahaudin, Ahmad Yusni; Kamaruddeen, Ahmed Mohammed (SAGE Publications, 2018)
Significant number of empirical research works have reported contravening results regarding the effects of organizational internal factors on construction risk management. This prompted the introduction of a moderator variable. This research tested the moderating role of rules and regulations on the relationships between organizational internal factors and construction risk management. Drawing on discouragement and organizational control theory, this research studied the effects of organizational internal factors and rules and regulations on construction risk management among 238 employees operating in Abuja and Lagos State construction companies in Nigeria. Self-administered questionnaires were used to gather the data. Using the partial least squares structural equation modelling (PLS-SEM) for analysis, a significant positive relationship between organizational internal factors and construction risk management was acknowledged. This study also discovered a significant positive relationship between rules and regulations and construction risk management. As expected, rules and regulations was discovered to moderate the relationship between organizational internal factors and construction risk management, with a significant positive result. A significant interaction effect was also discovered between rules and regulations and organizational internal factors. The significance of this study on Nigerian construction industry was also highlighted.